Cote d'Ivoire Joint Bank-Fund Debt Sustainability Analysis - 2018 Update - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Côte d’Ivoire has a moderate risk of external debt distress, with limited space to absorb shocks. All liquidity and solvency external debt indicators lie below their thresholds under the baseline scenario. However, the ratios of external debt service to revenue and exports are projected to rise, diminishing room to maneuver, and an export shock would cause breaches of their relevant thresholds under the worst-case stress scenarios. This underscores the substantial downside risks originating from external shocks and the need to boost domestic revenue mobilization. The overall risk of public debt distress is also moderate, with public debt to GDP ratio expected to decrease gradually. A sustained compliance with the WAEMU fiscal deficit convergence criterion and a prudent external borrowing strategy balancing the costs and economic return of new loans will be crucial to preserve debt sustainability.